Dampak Digital Marketing terhadap Produksi UMKM - Ammalia Shelky Nakwa; Pramudya Gandara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study intended to examine the impact of implementation’s digital marketing on the production level of Micro, Small, and Medium Enterprises (MSMEs). In the digital era, technology-based marketing strategies such as social media, e-commerce, and messaging applications have become essential tools for reaching a wider range of consumers. This research uses a qualitative approach with semi-structured interview techniques involving MSME actors from various sectors. The results show that most MSMEs actively utilizing digital marketing have experienced a significant increase in demand, which has led to higher production levels. However, some MSMEs have not felt a substantial impact due to limitations in managing digital platforms and a lack of knowledge in online marketing. Digital marketing plays an important role in supporting the growth of MSME production, although its effectiveness largely depends on the adaptability of each business owner. This research is expected to contribute to the preparation of digital marketing strategies for MSMEs in the digital era.